Crime organizado e seu tratamento jurídico penal - Godoy, Luiz Roberto Ungaretti de (2009)
This study is devoted to the elaboration of the evolution of Organized Crime in the national and international scenery and its main reflexes in our Country, based not only on the Brazilian Law, but also in the Foreign Law the Judicial Precedent, as well as the undoubtedly relevance of Treaties and Conventions linked to the subject. The Brazilian legislation does not consider the typical profile of a criminal organization, though the Brazilian Judicial ordainment has already consolidated in several laws which discipline, directly or indirectly the Organized Crime, once it is extremely important we should highlight the reception of the Brazilian Legal System of the Palermo Convention (United Nations Convention against Transnational Organized Crime).Which has adapted a definition for the transnational Criminal Organization. In the course this study we would try to perform an analysis of several organizations, associations, mafias, gangs, among others identified in the word scenery with a focus in the Organized Crime in Brazil. It s important to highlight that each of the criminal groups has its own characteristics taking on account its constitution and its peculates in the modus operandi, making it impossible to draw a draw a hermetic profile of each one. This way the target of the present study is not a search for a typical definition of a would be criminal organization, but to show the main characteristics of Organized Crime in the current scenery, based on the history of development and in the act themselves performed by these groups. At last we haven t left aside the great discussion which involves the subject which are the reflexes of the actions performed by the criminal transnational organizations, as well as the question of which criminal law to use once the groups mentioned act simultaneously in several different countries